Influence of B4C addition on the tribological properties of bronze matrix brake pad materials - Kuş Hüsamettin (Open Chemistry)
In this study, the effects of B4C particle addition on the microstructural, mechanical, and tribological properties of bronze matrix brake pad materials were analyzed. To this end, bronze matrix brake pads reinforced with different proportions (0, 3, 6, 9, and 12 wt%) of B4C particles were fabricated via hot pressing at 800°C and 40 MPa for 5 min. The hardness, density, and transverse rupture strength (TRS) were measured and friction–wear tests were performed to evaluate the effectiveness of adding B4C. The results revealed that the hardness increased with increasing B4C content, whereas the density slightly decreased. The TRSs of the B4C-reinforced specimens exceeded that of the non-reinforced material. Furthermore, the friction stability, average friction coefficient, and wear resistance, which are crucial quality parameters of the brake pad material, increased upon adding >3 wt% B4C to the specimen compared with those of the non-reinforced specimen. After the wear test, the worn surfaces of the specimens were examined via scanning electron microscopy, X-ray diffraction, and a 3D optical profilometer to identify the wear mechanisms involved during friction.